The Benefits of Nurturing EFL Teachers’ Agency at the Beginning of their Professional Development Journeys - Kristian Wijaya, (Journal of Language and Literature Studies, 2024)
EFL educators in this modern age are vulnerable to stressful and anxiety-evoking situations while dealing with their daily teaching demands such as heavy administrative workloads, unyielding students’ behaviors, and external pressure from the educational stakeholders. To better mitigate all these inevitable educational issues, it is of key importance for second language educators to instill a higher level of agency to nurture their commitment in giving their best teaching performances for their learners. For this reason, the researcher embarked this small-scale library study by exploring the potential benefits promoted by agency contributable for the further professional development within EFL educationalists. By doing so, the forthcoming research results can potentially promote a glimpse of enlightenment for globalized ELT stakeholders to better support the continual development of EFL teachers’ agency influential for the significant advancement of the whole second language exposure quality.  A library analysis methodology was selected to generate more credible, relatable, and applicable research results for the targeted educational parties. To fulfill this major specific research objective, the researcher particularly chose 20 previous EFL teachers’ agency literature having been published worldwide in varied reputable journal article platforms ranging from 2017 until 2023 year to yield more relevant research outcomes for the predetermined research fields. The thematically clustered research results highly encouraged globalized educational institutions to start prioritizing the constant development of EFL teachers’ agency to gradually transform them into more adaptable and highly dedicated educationalists.